1954
DOI: 10.1002/jsfa.2740050301
|View full text |Cite
|
Sign up to set email alerts
|

A technique for the approximate quantitative prediction of flat souring in canned peas

Abstract: It is shown that the percentage of canned peas that will sour on incubation a t 1 3 1 '~ ( 5 5 . 0 '~) may be predicted approximately by enumerating the flat-sour spores in unprocessed cans, expressing the cannery process in terms of decimal reduction times for flat-sour spores, calculating the number of surviving spores per can and from this the percentage spoilage. Graphs have been drawn to simplify the expression of processing times as decimal reduction times, and for calculating the percentage spoilage fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1968
1968
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…T A = 100°C in the calculations for Table 2. The choice of T A is arbitrary, but it can be shown that any value of ir, in the range 100-140°C results in a similar value of the ratio (tRl/tR2)1000 f Levine (1956), (b) Deindoerfer (1957), (c) Klostergaard (1965), (d) Ball & Olsen (1957), (e) Stumbo, Murphy & Cochran (1950), (f) Knock (1954). …”
Section: C Jonesmentioning
confidence: 95%
“…T A = 100°C in the calculations for Table 2. The choice of T A is arbitrary, but it can be shown that any value of ir, in the range 100-140°C results in a similar value of the ratio (tRl/tR2)1000 f Levine (1956), (b) Deindoerfer (1957), (c) Klostergaard (1965), (d) Ball & Olsen (1957), (e) Stumbo, Murphy & Cochran (1950), (f) Knock (1954). …”
Section: C Jonesmentioning
confidence: 95%